To simplify the product \( \sqrt{3} \times \sqrt{48} \), we can use the property of square roots which states that \( \sqrt{a} \times \sqrt{b} = \sqrt{a \times b} \).
So, we have:
\[ \sqrt{3} \times \sqrt{48} = \sqrt{3 \times 48} \]
Now, calculate \( 3 \times 48 \):
\[ 3 \times 48 = 144 \]
Thus, we can rewrite the expression:
\[ \sqrt{3} \times \sqrt{48} = \sqrt{144} \]
Now, we can simplify \( \sqrt{144} \):
\[ \sqrt{144} = 12 \]
Therefore, the simplified form of \( \sqrt{3} \times \sqrt{48} \) is:
\[ \boxed{12} \]